Regional economic issues : Central, Eastern, And southeastern Europe - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2016)
These reports discuss recent economic developments and prospects for countries in various regions. They also address economic policy developments that have affected economic performance in the regions, and discuss key challenges faced by policymakers. They address regional policy developments and challenges, and provide country-specific data and analysis, including through analytical pieces on issues of interest to a particular region.
It is published twice per year in the spring and the fall Some issues have thematic titles
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC POLICY; GOVERNMENT POLICY; EUROPE